(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2013)
Two thermophilic fungi, Thermomyces lanuginosus BPJ-10 and Rhizomucor pusillus BPJ-2 were studied under solid state fermentation (SSF) using wheat bran for the production of thermostable xylanase. The optimum time required for the production of xylanase was found to be 4 days and 7 days for R. pusillus BPJ-2 and T. lanuginosus BPJ-10 respectively. The optimum temperatures for the production of xylanase by R. pusillus BPJ-2 and T. lanuginosus BPJ-10 were 45°C and 50°C respectively. The maximum activity of xylanase (1.685 IU/ml and 0.075 IU/ml) was exhibited by T. lanuginosus BPJ-10 and R. pusillus BPJ-2 at pH 7.0 and pH 4.0 respectively. The optimum moisture content for maximum xylanase production was 90% for both fungi. J. Asiat. Soc. Bangladesh, Sci. 39(1): 43-51, June 2013 DOI: http://dx.doi.org/10.3329/jasbs.v39i1.16032